2001
DOI: 10.3390/i2050263
|View full text |Cite
|
Sign up to set email alerts
|

A First Principles Density Functional Study of Au Deposition on TiN (001) Surface

Abstract: Abstract:The structure and local electron properties of Au atoms deposited on the TiN (001) surface has been theoretically analyzed using a periodic slab model and density functional based calculations. The surface is described by means of a 2x2 cell five layers thick, on which gold atoms are added. Deposition of single atoms on the surface, (θ = 0.25 ML),shows that the preferred site is on-top of Ti atoms, with a metal-surface distance of 2.49 Å.The computed adsorption energy for this site is -1.92 eV, only s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…In previous studies, 37,40 it was found that various atoms and molecules, such as H, Au, and H 2 , are favorably adsorbed on the Ti atoms of a TiN surface. It therefore seems surprising that the Ru atom of RuCpPy is situated on top of the surface N s atom instead of the Ti s atom.…”
Section: ■ Theoretical Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In previous studies, 37,40 it was found that various atoms and molecules, such as H, Au, and H 2 , are favorably adsorbed on the Ti atoms of a TiN surface. It therefore seems surprising that the Ru atom of RuCpPy is situated on top of the surface N s atom instead of the Ti s atom.…”
Section: ■ Theoretical Resultsmentioning
confidence: 97%
“…In conclusion, the strong bond RuCpPy and the TiN surface arises from the interaction between a 2p orbital of N Py and one of the Ti s atoms and between the 4d orbitals of Ru and the 3d orbitals of three Ti s atoms, in agreement with literature findings for other adsorption reactions on the TiN surface. 37,40 The N Py −Ti s interaction contributes about −10.4 kcal/mol with PBE or −22.4 kcal/mol with vdW-DF, whereas the Ru−Ti s interaction contributes about −18.0 kcal/mol with PBE or −21.9 kcal/mol with vdW-DF (Figure 6).…”
Section: ■ Theoretical Resultsmentioning
confidence: 99%
“…The surface energy of bcc iron is reported to be 2.42 Jm −2 , but the specific facet to which this energy corresponds was not stated [27]. Whereas some earlier calculations have shown the (100) surface to be the most stable facet for bcc iron, controversy remains as to the relative stabilities of the (100) and (110) facets of other bcc metal surfaces [28][29][30] First principles DFT methods can be successfully employed to investigate monolayer (ML) deposition and the tuning of metal sur-face work functions, as studied earlier for example for Ag and Mo surfaces through the deposition of ultrathin oxide films [31] and the TiN (001) surface through the deposition of Au [32]. In line with these studies, the present work investigates the thermodynamically stable sites for nickel adsorption on to iron and their effect on the extent of surface relaxation, reconstruction and work function of the Fe (100), (110), and (111) surfaces in order to evaluate this procedure as a method to enhance iron surfaces for catalytic reactions, for example for the process of CO2 activation and reduction.…”
Section: Introductionmentioning
confidence: 99%